2019
DOI: 10.1186/s12967-019-2100-3
|View full text |Cite
|
Sign up to set email alerts
|

The tumor inflammation signature (TIS) is associated with anti-PD-1 treatment benefit in the CERTIM pan-cancer cohort

Abstract: BackgroundThe 18-gene tumor inflammation signature (TIS) is a clinical research assay that enriches for clinical benefit to immune checkpoint blockade. We evaluated its ability to predict clinical benefit of immunotherapy in cancer patients treated with PD-1 checkpoint inhibitors in routine clinical care.MethodsThe CERTIM cohort is a prospective cohort which includes patients receiving immune checkpoint inhibitors in Cochin University hospital. RNA extracted from 58 archival formalin fixed paraffin embedded tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 24 publications
6
87
2
Order By: Relevance
“…A previous study in lung cancer revealed a weak correlation between Tils with PD-L1 expression, but not with TMB [44]. While the sample size in this study was small, our study assessed the correlations of these three biomarkers in a larger size of sample with lung cancer.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study in lung cancer revealed a weak correlation between Tils with PD-L1 expression, but not with TMB [44]. While the sample size in this study was small, our study assessed the correlations of these three biomarkers in a larger size of sample with lung cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Blockade of PD-1 signaling by anti-PD-L1 antibody impaired the interaction between AML cells and Treg cells and improved diseases. It is generally recognized that PD-L1 is extensively detectable on the majority of tumors including solid and hematological malignancies (36,37). In AML, the PD-L1 overexpression usually occurred during therapy, after alloHSCT (38) and therapy with hypomethylating agents (39), such as azaticidine and decitabine, and at the relapse of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…31 Recently, the utility of such signature as an accurate and independent predictive biomarker has been validated in a pan-cancer study analyzing anti-PD-1 treatment benefit in primary tumors. 32 Thus, we propose to treat HIC metastases with immune checkpoint inhibitors, irrespective of their primary site of origin. In agreement, and close to be statistically significant, melanoma metastatic samples classified into HIC and MIC showed better OS than LIC after treatment with anti-PD1 inhibitors pembrolizumab or nivolumab.…”
Section: Open Accessmentioning
confidence: 99%